EyeTFDB: a Curated Eye Disease Transcription Factor Web-Based Platform - Ghorbani , Mahdiye; Meshkin, Alireza; Pournoor, Ehsan (Journal of Ophthalmic and Optometric Sciences, 2020)
Background: The TFs identify as distinct DNA sequences to regulate transcription processes and chromatin forming. Materials and Methods: To address needs in multiple areas, we present the EyeTFDB (https://eyetfdb.databanks.behrc.ir/) web-based platform, a novel platform of curated data. It combines the eye disease-related pathways data from the KEGG and REACTOME and their associated mRNAs. Furthermore, we expanded our mRNAs data by extracting disease-related data from valuable databases like DisGeNET and OMIM. Results: Despite the high importance of eye diseases and the global need for further research in this area, still, there is no remarkable comprehensive database for transcription factors of eye diseases. Here we integrated multiple heterogeneous datasets from different databases addressing this need. We collected 429 mRNAs from 1258 pathways for 25 types of eye disease. In addition, transcription factors are separated from this considerable amount of data. EyeTFDB user interface is designed to facilitate multiple types of the desired use: (i) the interactive investigations of individual entries on the level of a gene, transcription factor, pathway, eye disease, and (ii) the construction of highly customized datasets using advanced searching and filtering. Conclusion: The status of eye TFs and their broad interactions could significantly influence eye health. EyeTFDB, as well as other established databases serve as rich resources for assisting the researchers in exploring eye TFs in the elevation of public health. The wealthy information generated from future investigations can be incorporated into EyeTFDB for better serving the eye TF research and exploration efforts.